The barbershop renovation: prevention program of communicable diseases - Fikki Prasetya; Pradhea Wulandari (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2020)
Infectious diseases such as HIV / AIDS and hepatitis are diseases that can be transmitted through various media, one of them through shaving tools that are not hygienic which is still rarely noticed by barber. Barbershop renovation is an educational program which was designed as an effort to prevent infectious diseases in Barbershop through education with the use of mirror stickers and shaving cloth media and assistance during the program. The purpose of this research is to determine the effectiveness of Barbershop's surgical program against the prevention of infectious diseases through a shaver at Barbershop in Kendari City in 2019. This study used quasi-experimental designs with a treatment-control group design (pre-test and post-test). A total of 30 Barbershops were involved in the study, which were selected by purposive sampling technique. Data analysis used Wilcoxon sign rank test for testing the difference between before and after treatment, and mann whitney U test, for testing the differences between the treatment and control groups. The results of data analysis showed differences in attitudes both before and after treatment. In addition we also found significant differences between the treatment group and the control group. So it could be concluded that the operation of the Barbershop renovation program was effective in providing education and influence the attitude about preventing transmission of infectious diseases through shavers. Suggestions that can be given are strengthening health strategies, like supervisory support and training is needed to facilitate effective preventive measures against infectious diseases among barbers